Communism and State. An invitation to discuss outside orthodoxy - Guastini, Riccardo (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
Rereading. Originally published as “Comunismo e stato. An invitation to discuss fuori dell 'ortodossia” in Problemi del socialismo, n.9, Anno XIX, 1978, pp. 79-97. Translation by Hernán G. Bouvier (CONICET-UNC. Argentina)